2022
DOI: 10.3390/molecules27248832
|View full text |Cite
|
Sign up to set email alerts
|

Nanosilica-Anchored Polycaprolactone/Chitosan Nanofibrous Bioscaffold to Boost Osteogenesis for Bone Tissue Engineering

Abstract: The strategy of incorporating bioactive inorganic nanomaterials without side effects as osteoinductive supplements is promising for bone regeneration. In this work, a novel biomass nanofibrous scaffold synthesized by electrospinning silica (SiO2) nanoparticles into polycaprolactone/chitosan (PCL/CS) nanofibers was reported for bone tissue engineering. The nanosilica-anchored PCL/CS nanofibrous bioscaffold (PCL/CS/SiO2) exhibited an interlinked continuous fibers framework with SiO2 nanoparticles embedded in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Previous research has reported the successful electrospinning method to obtain the composite of polycaprolactone/chitosan, the nanofibers have a diameter of 50–100 nm with smooth surfaces and interconnected microstructure that will beneficial for easier cell penetration into pores of bioscaffolds . Furthermore, incorporating SiO 2 into the PCL/chitosan scaffold will increase hydrophilicity of the scaffold, raising the cell proliferation ability and decreasing cell contamination to create a favorable environment for bone tissue regeneration …”
Section: Chitosan-based Biomaterials For Bone Scaffoldmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has reported the successful electrospinning method to obtain the composite of polycaprolactone/chitosan, the nanofibers have a diameter of 50–100 nm with smooth surfaces and interconnected microstructure that will beneficial for easier cell penetration into pores of bioscaffolds . Furthermore, incorporating SiO 2 into the PCL/chitosan scaffold will increase hydrophilicity of the scaffold, raising the cell proliferation ability and decreasing cell contamination to create a favorable environment for bone tissue regeneration …”
Section: Chitosan-based Biomaterials For Bone Scaffoldmentioning
confidence: 99%
“…52 Furthermore, incorporating SiO 2 into the PCL/chitosan scaffold will increase hydrophilicity of the scaffold, raising the cell proliferation ability and decreasing cell contamination to create a favorable environment for bone tissue regeneration. 124 TIPS can also be an option to produce a chitosan nanofiber with a size between 50 and 500 nm. 125 Zhu et al combined TIPS and 3D printing technology to obtain the composite of porous poly(L-lactide) (PLLA) and chitosan nanofiber and then combined it with polydopamine (PDA) and functionalized with quercetin (Qu).…”
Section: Chitosan-based Biomaterials For Bone Scaffoldmentioning
confidence: 99%
“…The scaffold's physical properties (e.g., surface roughness, development of the specific surface area) [315] play a critical role in providing cell anchorage [16]. Successful anchoring enables effective cell adhesion [316]. Cell adhesion allows cells to stick to the scaffold's surface through specific molecular interactions, promotes cell proliferation, and enables cell differentiation through the development of a specific surface area [251,317].…”
Section: Surface Propertiesmentioning
confidence: 99%
“…Silicon stimulates bone formation, either by promoting the secretion of factors, the osteogenic differentiation, and the mineralization process ( Chen D. et al, 2022 ; Chen et al, 2022 X. ; Ge et al, 2022 ; Yunsheng et al, 2023 ) or by regulating the osteoclastogenic activity ( Schröder et al, 2012 ; Magnusson et al, 2021 ). Since the development of bioactive glass 45S5 by Hench in the 1960s, different compositions of silicon-based glasses have been developed and evaluated for applications in bone regeneration.…”
Section: Introductionmentioning
confidence: 99%